Designing & building a solar house : Your place in the sun - Watson, Donald, 1937- (Charlotte, Vt. : Garden Way Pub., 1977)
A look at solar designs and equipment that can save both fuel and construction costs on a new or existing house.
Includes bibliographical references (p. 207-209) and index.
Keywords: Solar heating; Solar houses -- Design and construction